Frederick Ashton and his Ballets Book review - Simpson, Jane (Dance Books Ltd., Alton,Hampshire (UK), 1999)
PALABRAS CLAVE: Frederick Ashton, Julie Kavanagh.
Frederick Ashton and his Ballets. David Vaughan, Dance Books, 1999.